Penerapan Root Cause Analysis pada Penurunan Kinerja Karyawan - Mega Astuti DR; Uwes Anis Chaeruman; Mulyadi (Jurnal Pembelajaran Inovatif, 2019)
This study aims to find out the root cause of the decreasing human performance and provide the right interventions to solve the problem in project payment sub division at PT. Sedayu Utama. The research method used is descriptive analysis with qualitative approach, data is obtained through interview, questionnaire and observation. As the results of this study of root cause analysis, the inability to use electronic equipment, to accept constructive criticism due to high level of superiority and lack of initiative thinking are found. Meanwhile from equipment factor such as computer and scanner, it is found to be underutilized and from management factor, it is found that there’s a lack of commitment, competition, coordination and understanding of the company’s procedure, from motivation factor, it is found that there’s a lack of supervision, reward & punishment and lack of value inconsistent with mission. The solutions advised to solve these problems are coaching, knowledge management, sharing session, on the job training and reward & punishment.